4. 1) ![\frac{2x^{2}+7 }{2x-5} = x-4 \frac{2x^{2}+7 }{2x-5} = x-4](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E%7B2%7D%2B7%20%7D%7B2x-5%7D%20%3D%20x-4)
,x ≠ ![\frac{5}{2} \frac{5}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B2%7D)
2x²+7 = (x-4) * (2x-5)
2x² + 7 = 2x² - 5x - 8x + 20
7 = -5x - 8x + 20
7 = -13x + 20
13x = 20-7
13x=13
x = 1, x ≠ ![\frac{5}{2} \frac{5}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B2%7D)
x = 1
2) ![\frac{3x^{2} -8}{3x+2} = x-2 \frac{3x^{2} -8}{3x+2} = x-2](https://tex.z-dn.net/?f=%5Cfrac%7B3x%5E%7B2%7D%20-8%7D%7B3x%2B2%7D%20%3D%20x-2)
, x≠![-\frac{2}{3} -\frac{2}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B3%7D)
3x² - 8 = (x-2) * (3x+2)
3x² - 8 = 3x² + 2x - 6x - 4
- 8 = 2x - 6x -4
-8 = -4x-4
4x = - 4 + 8
4x = 4
x = 1, x≠![-\frac{2}{3} -\frac{2}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B3%7D)
x = 1